Perkawinan Campur Antara Etnis Jawa Dengan Etnis Aceh Di Kecamatan Pante Ceureumen Kabupaten Aceh Barat - Sopar Sopar; Arfriani Maifizar (Jurnal Community, 2020)
The title is "Mixed Marriage Between Javanese and Acehnese Ethnics in Pante Ceureumen District, West Aceh Regency". The research problem is how the process of mixed marriages between Javanese and Acehnese ethnics in Pante Ceureumen District, West Aceh Regency. The purpose of writing is to determine the implementation of intermarriage between Javanese and Acehnese in Pante Ceureumen District, West Aceh Regency. The research method used is ethnographic research methods or reports on an ethnic group, which are written based on the results of field research and use a "gradual progression". In this study, the authors concentrate on one of the stages, namely finding cultural themes. The main data of this research is qualitative data obtained through interviews with mixed married couples. Data collection techniques used include observation techniques, interview techniques. The data analysis process was carried out since the data collection in the field took place in stages and was described in writing. The conclusion of the research obtained is that mixed marriages between Javanese and Acehnese in Pante Ceureumen District are carried out through socio-economic relations, socio-political relations and socio-cultural relations and are driven by factors of similarity in education, occupation, place of residence, religion and also because of a mate. and arranged marriage. The implementation of mixed marriages between Javanese and Acehnese ethnics in Pante Ceureumen District, uses the customs of the two ethnicities. The traditional mixed marriage culture between Javanese ethnicities that is still being carried out includes the stage of proposing, fiance, seeds, bebet and weights as well as the wedding party. Meanwhile, the traditional mixed marriage culture that is carried out includes the stage of meulakee, ranub kong haba, ranub gaca, gatib, intat linto and tung dara baro.